Does board behaviour matter for board effectiveness in Small and Medium Industries (SMEs)?: a preliminary observation - Adi, Nazir; Mohamad, Arifha; Wan Yusoff, Wan Fauziah (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2022)
The issue of corporate governance affects big corporations and small businesses. Maintaining a well-functioning board of directors in small and medium-sized enterprises (SMEs) is one of the most effective ways of increasing the efficacy of the board. This article examines previous studies on board behaviour that are critical to the effectiveness of boards of directors in small and medium-sized enterprises (SMEs). Previous literature found several attributes of directors that need to be nurtured. Having a different view relating to the task in a boardroom, preparedness, involvement, use of specific knowledge and skills are among them. In short, more empirical studies relating to these antecedents are recommended to understand board behaviour better, especially when making a decision.